ACTIVITY OF AVOCADO SEED PROTEIN AGAINST CANCER CELL LINES - INDRAYUDHA, PENI; OKTASARI, SHOLIKHAH ROSVITA; IMANNI, NOBELLIA RAHMANDA; ARIANTI, NATASYA SALMAA; ANTAZULA, KHISAN; SEPTIANI, TIARA (International Journal of Applied Pharmaceutics, 2025)
Objective: The purpose of this study was to determine the anticancer activity of avocado seed protein against HeLa, 4T1, MCF7, and Vero cells and the protein profile by SDS-PAGE. Methods: The active protein fraction of avocado seeds was purified by column chromatography method with diethylaminoethyl ion exchange matrix (DEAE) and hydrophobic matrix such as butyl. Isolation was carried out on both matrices and the concentration of the active protein fraction of avocado seeds was read using Biodrop. Protein profile identification was obtained by SDS-PAGE. Cytotoxic tests were carried out using the MTT assay. IC50 was used to determine the cytotoxicity of the samples, while the amount of doubling time was measured to define the antiproliferative activity of the protein at hours 24, 48, and 72. Results: Cytotoxic test results showed that the protein fraction of avocado seed purified with butyl matrix with showed has potent cytotoxic activity in MCF-7 cells with an IC50 of 12.21 µg/ml, and to 4T1 cells with IC50 5.42 µg/ml, and did not have cytotoxic activity in HeLa cells, also did not have the antiproliferation activity of MCF-7 cells. The protein fraction concentration range tested was 7.125-57 µg/ml. The protein fraction from the DEAE matrix was not cytotoxic to HeLa, MCF-7, and 4T1 cells. The activity of avocado seed protein isolate using DEAE and butyl matrices against Vero cells was categorized as non-toxic because the average percentage of viable cells is more than 50%. The results of the doubling time value of the avocado seed fraction to 4T1 cells were 5.78 h while the control cells of Vero cells were 98.75 h. The analysis using SDS-PAGE showed the formation of protein bands in the fractionated avocado seeds that have a molecular weight between 25-30 kDa and this protein is included in category RIPs (Ribosom Inactivating Proteins) type 1. Conclusion: The protein fraction of avocado seed from butyl matrix has cytotoxic activity on MCF7 and 4T1 cell lines, while from DEAE matrix has no cytotoxic activity on HeLa, MCF-7 and 4T1 cells. Protein fraction also has antiproliferative activity on 4T1 cell lines. The protein fraction of avocado seeds containing RIPs type 1. This protein fraction has the potential to be developed as an anticancer but require further purification regarding the activity of the active fraction on cancer cells to ensure the activity and selectivity.